Primary menouria due to a congenital Urethrovaginal fistulawith vaginal agenesis - Razzak, Lubna; Rizvi, Raheela Mohsin (Nepal Journal of Obstetrics and Gynaecology, 2018)
Case: A female aged 22 years, suffering from cyclical menouria since age of 12 years presented to our clinic with concerns for future sexuality and fertility. Clinical examination revealed the absence of a vagina, although labia minora and majora were adequately developed. Secondary sexual growth such as axillary and pubic hair, breast development was normal. Micturating cystogram shows abnormal fistulous communication between the posterior urethra and upper vagina with contrast outlining the uterine cavity. Magnetic resonance imaging revealed functioning left kidney along with vaginal agenesis and an abnormal communication between uterus and urethra. The surgical treatment included urethrovaginal fistula repair and pull through vaginoplasty. The patient was asymptomatic till her last visit Conclusions: In this case, the diagnosis of congenital urethrovaginal fistula was delayed until adulthood despite menouria. This is a rare case report and to our best of literature search .we could not find any such case report.